1976
DOI: 10.1007/bf00428978
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic blood flow in conscious dogs after oral administration of glucose

Abstract: Dogs with electromagnetic flowprobe implanted around the superior pancreaticoduodenal artery and with an hydraulic occluder implanted upstream from the flowprobe were examined between the 3rd and the 8th postoperative day. During an oral glucose load, blood flow increased from the beginning of administration to about 25 minutes, but not when blood glucose and plasma IRI exhibit their maxima. The rise of pancreatic blood flow is assumed to be produced by reflexes similar to those stimulating insulin secretion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Early attempts to investigate the islet microcirculation with intravital microscopy suggested that wide variations occur in the blood flow to the islets, which seemed related to the functional state of the B cells [1,4,5,28]. More recent studies indicate that blood flow to the whole pancreas may increase under conditions which stimulate insulin release [6,7,33], but these observations have been difficult to interpret, since the endocrine and exocrine parts of the gland may not share the same mechanisms for regulating blood flow [35].…”
mentioning
confidence: 99%
“…Early attempts to investigate the islet microcirculation with intravital microscopy suggested that wide variations occur in the blood flow to the islets, which seemed related to the functional state of the B cells [1,4,5,28]. More recent studies indicate that blood flow to the whole pancreas may increase under conditions which stimulate insulin release [6,7,33], but these observations have been difficult to interpret, since the endocrine and exocrine parts of the gland may not share the same mechanisms for regulating blood flow [35].…”
mentioning
confidence: 99%